Differences in Fatty Acids and Lipids of Massive and Branching Reef-Building Corals and Response to Environmental Changes - Liu, Chengyue; Zhang, Yuyang; Huang, Lintao; Yu, Xiaolei; Luo, Yong; Jiang, Lei; Sun, Youfang; Liu, Sheng; Huang, Hui (Frontiers in Marine Science, 2022)
Reef-building corals present various colony morphologies that may greatly influence their nutritional ecology. Fatty acids (FAs) and lipids are important components of corals and have been increasingly used to research the nutritional ecology of corals. In this study, we examined the symbiodiniaceae density, corallite area, total lipid content, and FAs composition of 14 species of corals with different colony morphologies. The results showed that the different colony morphology of coral was significantly correlated with the corallite area but not with the symbiodiniaceae density. Massive corals, with a large corallite area (7.16 ± 6.29 mm2), could ingest a high quantity of food, leading to high levels of total lipid content and unsaturated FAs [particularly n-6 polyunsaturated FAs (PUFAs) and monounsaturated FAs]. For branching corals, the total lipid content and saturated FAs (SFAs, 16:0 and 18:0) were significantly positively correlated with the Symbiodiniaceae density, indicating that branching corals are predominantly autotrophic. Moreover, compared with healthy corals, bleached corals consume larger amounts of stored energy (such as lipids and SFAs) to maintain their normal physiological functions. Although bleached corals may obtain PUFAs from heterotrophic assimilation or biosynthesize, the efficiency is too low to sufficiently replenish essential PUFAs in a short time. Overall, massive corals with more initial total lipid content and PUFAs exhibit an advantage under adverse environmental conditions.